Synthesis of Porous Biochar Containing Graphitic Carbon Derived From Lignin Content of Forestry Biomass and Its Application for the Removal of Diclofenac Sodium From Aqueous Solution - Tam, Nguyen Thi Minh; Liu, Yun-guo; Bashir, Hassan; Zhang, Peng; Liu, Shao-bo; Tan, Xiaofei; Dai, Ming-yang; Li, Mei-fang (Frontiers in Chemistry, 2020)
Porous biochar containing graphitic carbon materials have received great attention from various disciplines, especially for environmental pollutant treatment due to their cost-effective and specific textural properties. This study exhibited a two-step strategy to compose lignin-porous biochar containing graphitic carbon (LPGC) from pitch pine sawdust and investigated its adsorptive removal for diclofenac sodium (DCF) from aqueous solution. Sulfuric acid (H2SO4) was utilized to obtain lignin content from biomass and potassium ferrate (K2FeO4) was adopted to fulfill the synchronous carbonization and graphitization of LPGC. Through slow pyrolysis in atmospheric N2 (900oC – 2 hours), the structure of as-prepared sample was successfully modified. By SEM images, stripped layer structure was observed on H2SO4-treated sample for both one-step and two-step activated samples, indicating the pronounced effect of H2SO4 in the layering of materials. K2FeO4 acted as an activator and catalyst to convert biomass into the porous graphitic structure. The BET surface area, XRD and Raman spectra analyses demonstrated that LPGC possessed a micro/meso porous structure with a relatively large surface area (457.4 m2 g-1) as well as the presence of graphitic structure. Further adsorption experiments revealed that LPGC exhibited a high DCF adsorption capacity (qmax=159.7 mg g-1 at 298 K, pH=6.5). The effects of ambient conditions such as contact time, solution pH, temperature, ionic strength, electrolyte background on the uptake of DCF were investigated by a batch adsorption experiment. Results indicated that the experimental data were best fitted with the pseudo second - order model and Langmuir isotherm model. Besides, the adsorption of DCF onto LPGC process was spontaneous and endothermic. Electrostatic interaction, H-bonding interaction, and π-π interaction are the possible adsorption mechanisms. The porous biochar containing graphitic carbon obtained from the lignin content of pitch pine sawdust may be a potential material for eliminating organic pollutants from water bodies.